PENGARUH KOMPLEKSITAS TUGAS DAN BEBAN KERJA TERHADAP KINERJA AUDITOR - Sososutiksno, Christina; Sapulette, Shella Gilby; Tutuarima, Yonry Gerald (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, 2022)
This study aims to determine the influence of task complexity and workload on the performance of auditors at the BPKP representative office in Maluku Province using a quantitative approach. The respondents to this study were 62 BPKP auditors. The sampling technique used is saturated sampling. The data used are primary data with the dissemination of questionnaires to respondents. Of the 62 questionnaires distributed, only 43 were returned and analyzed later. The data were analyzed using SPSS analysis 24. The results showed that the complexity of tasks and workload negatively affect the performance of auditors